The impact of the Arabs in spreading Islam and the Arab-Islamic civilization through the Silk Road (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, who bestowed favor upon humanity by sending the Seal of the Prophets, and prayers and peace be upon Muhammad bin Abdullah, the envoy as a mercy to the worlds, and upon all his companions.My research was entitled (The Impact of the Arabs in the Spread of Islam and the Arab-Islamic Civilization through the Silk Road). Because this subject is of great importance in the spread of Islam through the means of the silk trade, and through my followers many sources to give the subject its full due. As the topic was important in mentioning the Holy Quran and the role played by Arab Muslim travelers in the transfer of Arab Islamic civilization.The research included an introduction and two topics:The first topic: the spread of Islam and the role of travelers.The second topic: Trade and the extent of its activity and its importance in the spread of Islam and the Arab-Islamic civilization.Then came the conclusion of the most important findings, which were included after itMargins, then sources and references, and finally the summary in English.As for the sources that I used in writing the research, which are: (The Holy Qur’an, Al-Alusi - History of Islam in Africa and Southeast Asia, Arnold - The Call to Islam, Ibn Khordadbeh - Tracts and Kingdoms, Al-Jahiz - Insight into Trade, Al-Hamwi - Lexicon of Countries, Al-Hamarna - The Role of the Idiot In Gulf Trade, Al-Hajji - Islamic Civilization in Andalusia, Hassan - The Journey among the Arabs, Demombene - Islamic Systems, Ziyadah - Development of Trade and Maritime, Al-Samer - Historical Origins of Arab-Islamic Civilization in the Far East, Al-Ali - History of Arab-Islamic Civilization, Awad - Role of Arabs The Gulf in the Spread of Islam in Southeast Asia, Al-Ani - Oman in the early Islamic eras, Lubon - Arab Civilization, Al-Masoudi - Akhbar Al-Zaman - Promoter of Gold and Mu’awin Al-Jawhar, Metz - Islamic Civilization in the Fourth Hijri Century, Markopolo - His Adventures and Explorations, Al-Nadawi - History of Prayers Between India and the Arab Countries, Al-Hamdhani - Baghdad, City of Peace).